Mycobacterium tuberculosis ribosomal protein S1 (RpsA) and variants with truncated C-terminal end show absence of interaction with pyrazinoic acid - Vallejos-Sanchez, Katherine (2020)
Pyrazinamide (PZA) is an antibiotic used in first- and second-line tuberculosis treatment regimens. Approximately 50% of multidrug-resistant tuberculosis and over 90% of extensively drug-resistant tuberculosis strains are also PZA resistant. Despite the key role played by PZA, its mechanisms of action are not yet fully understood. It has been postulated that pyrazinoic acid (POA), the hydrolyzed product of PZA, could inhibit trans-translation by binding to Ribosomal protein S1 (RpsA) and competing with tmRNA, the natural cofactor of RpsA. Subsequent data, however, indicate that these early findings resulted from experimental artifact. Hence, in this study we assess the capacity of POA to compete with tmRNA for RpsA. We evaluated RpsA wild type (WT), RpsA A438, and RpsA A438 variants with truncations towards the carboxy terminal end. Interactions were measured using Nuclear Magnetic Resonance spectroscopy (NMR), Isothermal Titration Calorimetry (ITC), Microscale Thermophoresis (MST), and Electrophoretic Mobility Shift Assay (EMSA). We found no measurable binding between POA and RpsA (WT or variants). This suggests that RpsA may not be involved in the mechanism of action of PZA in Mycobacterium tuberculosis, as previously thought. Interactions observed between tmRNA and RpsA WT, RpsA A438, and each of the truncated variants of RpsA A438, are reported.